The Semantic Field of the Lexical Units “Hope,” “Trust,” and “Faith” in the Uzbek Language and Their Discursive Usage (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the semantic field of the lexical units “hope,” “trust,” and “faith” in the Uzbek language and examines their usage in various types of discourse. The study analyzes lexical meanings, semantic components, and stylistic-pragmatic aspects, highlighting the distinctive manifestations of these words in literary, religious, socio-political, and everyday speech contexts. The findings reveal that “hope” is expressed as a tendency or aspiration toward the future, “trust” as reliance and assurance in the present situation, and “faith” primarily within the sphere of religious or ideological belief. The semantic and pragmatic distinctions among these words provide a deeper understanding of their cultural and social significance in the Uzbek language.